Health Risk Assessment of Benzoic and Sorbic Acids Exposure from the Consumption of Rice Noodles among a University’ students - Sornsupab, Uraiporn; Sripa, Anutsara; Kongpran, Jira; Makkaew, Prasert (Thai Journal of Toxicology, 2020)
This study aimed to analyze the quantity of two preservatives, benzoic acid and sorbic acid in 3 types of rice noodles, namely wide rice noodles, rice stick noodles, and rice vermicelli. Thirty samples of rice noodles from 10 noodle shops sold at Walailak University in Nakhon Si Thammarat were analyzed by using High Performance Liquid Chromatography (HPLC). Health risks of students were assessed based on the amount of preservatives exposure compared to the acceptable daily intake (ADI). Benzoic acid was detected in 27 samples (90%), ranging from 0.85 to 666.90 mg/kg, while sorbic acid was detected in 13 samples (43.33%), ranging from 0.5 to 359.43 mg/kg. The maximum average benzoic acid content was found in the wide rice noodle samples (mean = 234.65 ± 111.07 and median = 269.52), and the maximum average amount of sorbic acid was found in the samples of rice stick noodle samples (mean = 107.20 ± 124.76 and median = 62.8); however, the amount of those 2 preservatives detected does not exceed the standard criteria according to the notification of the Ministry of Public Health. The results of health risk assessment among the students in the case of worst-case scenarios (the highest frequency and amount of consumption were used for calculation) exceeded the acceptable level in the case of both average and high risks, with the highest value in the case of high risk of exposure to benzoic acid and sorbic acid 981.30 and 195.02 of ADI, respectively. ...